Breastfeeding, bottle feeding and risk of malocclusion in mixed and permanent dentitions: a systematic review - Lucas Guimarães ABREU; Saul Martins PAIVA; Isabela Almeida PORDEUS; Carolina Castro MARTINS (Brazilian Oral Research, 2016)
Abstract The aim of the present study was to search for scientific evidence concerning the association between breastfeeding and bottle feeding and risk of malocclusion in mixed and permanent dentitions. An electronic search was performed in eight databases up to February 2015. Additionally, a gray literature search and hand searches of the reference lists of the selected studies were also carried out. There were no restrictions on language or on year of publication. The methodology of the included articles was evaluated using the Newcastle Ottawa scale. Out of the 817 identified citations, six studies fulfilled the eligibility criteria and were included in the systematic review. One study showed that children with mixed and permanent dentitions breastfed for more than 6 months presented greater mean protrusion of mandibular incisors and inclination of maxillary incisors compared with those breastfed for less than 6 months or those who were bottle-fed (p < 0.05). One study revealed that breastfeeding and bruxism were associated with Class II [OR = 3.14 (1.28 - 7.66)] and Class III [OR = 2.78 (1.21 - 6.36)] malocclusion in children with permanent dentition, while another study showed that an increase in breastfeeding duration was associated with a lower risk of malocclusion in children with both mixed and permanent dentitions (p < 0.001). Three studies did not report any significant association. Risk of bias was high in most selected articles. These findings do not support an association between breastfeeding and bottle feeding and the occurrence of malocclusion in mixed and permanent dentitions.